Structure design and rice threshing performance of the variable-speed inertial pulley for simulating artificial threshing - Jing, Tiantian; Tang, Zhong; Hao, Shuaihua; Shen, Cheng; Wang, Ting; Wang, Meilin (International Journal of Agricultural and Biological Engineering, 2024)
Due to the small models and compact structures, small harvesters have also caused problems such as poor threshing separation performance and large loss rates. In order to solve unstable cleaning effects of small harvesters when they facing different working conditions, this paper selected rice plants in hilly areas for the experiment. Tensile breaking force of different parts of mature rice was tested, which revealed the fracture mechanism of each part under the combined force. Inertial threshing method was used to simulate artificial plate bin and design three kinds of non-circular pulley variable speed transmission threshing mechanism. With the help of transient inertia force, threshing force was compensated. This paper tested the harvesting performance of the variable speed threshing device with the help of the harvest performance test. Results show when facing the small rice planting area, the T/2 variable speed threshing device has better cleaning performance, and also the harvest loss rate of T/4 variable speed threshing device is the lowest. Compared with the constant speed threshing device, the impurity content rate of the variable speed threshing device is increased by 0.64% to 8.76%; the loss rate is reduced by 0.45% to 1.79%, which provides a basis for the optimization design of small combine harvester in hilly areas.Keywords: small harvesters, fracture mechanism, transient inertia force, non-circular pulleyCitation: Jiang T T, Tang Z, Hao S H, Shen C, Wang T, Wang M L. Structure design and rice threshing performance of the variable-speed inertial pulley for simulating artificial threshing. Int J Agric & Biol Eng, 2024; 17(1): 33-40.